TEOREMA DENSITAS PADA HIMPUNAN SEMUA BILANGAN SAMAR - Erik Maurten Firdaus; M. Adib Jauhari Dwi Putra; Findasari Findasari (Universitas Muhammadiyah Kudus, 2024)
A fuzzy number is a fuzzy set with some special properties. In this paper, we defined some orderings on the set of all fuzzy numbers. We proved the Density Theorem on the set of all fuzzy numbers with an ordering . We showed that between any two fuzzy numbers, there exists a trapezoidal fuzzy number.